Decomposition of a minke whale carcass in a temperate dune ecosystem - Martin J. Baptist; Martin J. Baptist; Mardik F. Leopold; Marinka E. B. van Puijenbroek; Hans Verdaat; Nicole Janinhoff-Verdaat; Dennis R. Lammertsma; Wim J. Dimmers; Paul F. A. M. Römkens; Jan Burgers (Frontiers in Marine Science)
Due to the benefits to the ecosystem there is a growing incentive to limit management interventions of stranded whales. This study was conducted to test the impact of a stranded whale carcass decomposing in a natural dune ecosystem and to gain experience in managing a beached whale carcass. A 4.70 m male juvenile minke whale Balaenoptera acutorostrata carcass washed up on the western side of the uninhabited island Rottumerplaat, the Netherlands. The carcass was moved the same night into the dunes to prevent it from washing back into the sea. Regular field visits were undertaken and wildlife trail cameras were placed to document the decomposition stages and the attraction of avifauna. Pitfall traps were placed to monitor insect fauna next to the carcass. Vegetation plots were surveyed to document changes to the dune vegetation and soil cores were taken to determine the increase in metal, carbon and nutrient contents. Decomposition of the carcass until the bare skeleton within the temperate dune ecosystem took about two years. The carcass was highly beneficial for beetle biodiversity, attracting different beetle species at various stages of decomposition. In total, 129 species of beetles were found near the carcass, of which eight species are specific for carcasses. For scavenging birds such as gulls, magpies and carrion crows the skin of the minke whale was too tough to break open. While the initial nutrient leakage from the carcass was toxic to dune plants immediately around the carcass, it eventually promoted lush vegetation growth due to increased fertility. The bioavailable metal contents in the soil for potassium (K) and nickel (Ni) showed a significant increase due to the presence of the whale carcass up to six months. Significantly increased levels of arsenic (As), cobalt (Co) and vanadium (V) were found up to one and a half years later and sodium (Na) and manganese (Mn) persisted in elevated levels up to two years later. Recommendations were given on management interventions when leaving a whale carcass on site.